Diagnostic accuracy of pre-operative prediction of ovarian malignancy - Joshi, Rijuta (Journal of Patan Academy of Health Sciences, 2025)
Introduction: Pre-operative differentiation of ovarian neoplasm is essential to guide optimal management of women with ovarian masses. This study was done to evaluate the diagnostic accuracy of clinical examination, Risk of Malignancy Index (RMI-3), Sassone score, International Ovarian Tumor Analysis (IOTA) simple rules, and Ovarian-Adnexal Reporting and Data System (O-RADS) in differentiating benign and malignant ovarian tumors.Method: A prospective cross-sectional descriptive study was conducted among 213 women at a tertiary care hospital in Nepal over two years (10th May 2023 – 23rd May 2025) after the ethical approval. Women with ovarian masses who were scheduled for surgery with complete preoperative CA-125 and ultrasound assessments were included in the study. Chi-square test was used to determine the statistical significance of diagnostic performance and p